2005
DOI: 10.1016/j.ejvs.2005.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Complications Related to Intra-aortic Balloon Pump in Cardiac Surgery: A Decade Later

Abstract: The study demonstrated a significant decrease in the IABP-related complications even though complexity of cases referred for surgery has increased. Henceforth, the risk of 1% vascular complications should play little influence on decision-making regarding the use of IABP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 10 publications
3
24
0
3
Order By: Relevance
“…[1,2] Also, it has been clear that IABP is an effective means of supporting failing circulation in patients at high risk of cardiovascular events post-operatively. [3] However, IABP is an intensive care-based treatment and is therefore costly. In addition, it can be accompanied by complications including limb ischemia, aortic or iliac dissection bleeding, infection, hemolysis, paraplegia, and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Also, it has been clear that IABP is an effective means of supporting failing circulation in patients at high risk of cardiovascular events post-operatively. [3] However, IABP is an intensive care-based treatment and is therefore costly. In addition, it can be accompanied by complications including limb ischemia, aortic or iliac dissection bleeding, infection, hemolysis, paraplegia, and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…An American study reported incidence levels ranging between 7.2 and 47% of vascular complications in cases of IABP use (5) . In 2000, a study In this study, as opposed to other sources (6)(7) , f e m a l e p a t i e n t s r e v e a l e d f e w e r r i s k s o f complications than men. A study published in 2000 demonstrated, using multivariate analysis, that the female gender, peripheral vascular disease and high body mass index (BMI) were independent predictors for the appearance of complications (8) .…”
Section: Clinical and Demographic Characteristicsmentioning
confidence: 85%
“…Only "sheathless" systems were used in the Heart and Diabetes Centre, North-RhineWestfalia, to minimize occlusion of the femoral vessels, and the balloon is placed just distal to the left subclavian artery. Use of small (8 French), sheathless catheters, and percutaneous insertion is associated with less complications (Elahi et al, 2005). …”
Section: A Percutaneous Insertion: Percutaneous Insertion Is Performedmentioning
confidence: 99%